Polymyxin B1 and E2 From Paenibacillus polymyxa Y-1 for Controlling Rice Bacterial Disease - Wenshi Yi; Wenshi Yi; Chao Chen; Xiuhai Gan (Frontiers in Cellular and Infection Microbiology, 2022)
To discover novel microbial pesticide for controlling rice bacterial disease, polymyxin B1 and E2 were firstly isolated from the supernatant of fermentation broth of Paenibacillus polymyxa Y-1 by bioactivity tracking separation. It is shown that polymyxin B1 and E2 had remarkable in vitro inhibitory activities to Xanthomonas oryzae pv. oryzae (Xoo) and Xanthomonas oryzae pv. oryzicola (Xoc) with the EC50 values of 0.19 μg/ml and 0.21 μg/ml against Xoo, and 0.32 μg/ml and 0.41 μg/ml against Xoc, respectively, which were better than those of Zhongshengmycin (0.31 μg/ml and 0.73 μg/ml) and Bismerthiazol (77.48 μg/ml and 85.30 μg/ml). Polymyxins B1 and E2 had good protection and curative activities against rice bacterial leaf blight (BLB) and rice bacterial leaf streak (BLS) in vivo. The protection and curative activities of polymyxins B1 (45.8 and 35.8%, respectively) and E2 (41.2 and 37.0%, respectively) to BLB were superior to those of Zhongshengmycin (34.8 and 29.8%, respectively) and Bismerthiazol (38.0 and 33.5%, respectively). Meanwhile, the protection and curative activities of polymyxins B1 (44.8 and 39.8%, respectively) and E2 (42.9 and 39.9%, respectively) to BLS were also superior to those of Zhongshengmycin (39.7 and 32.0%, respectively) and Bismerthiazol (41.5 and 34.3%, respectively). Polymyxin B1 exerted the anti-pesticide properties via destroying the cell integrity of Xoo, reducing its infectivity and enhancing rice resistance against pathogens through activating the phenylpropanoid biosynthesis pathway of rice. It is indicated that polymyxin B1 and E2 were potential microbial pesticides for controlling rice bacterial disease.